No-till in rice systems: A global meta-analysis of key agronomic practices impacting yields - Mia Godbey; Ignacio Macedo; Cameron M. Pittelkow; Bruce Linquist (Field Crops Research, 2026)

Multifactor analysis of land use transitions in a drought-affected rice region - Luke A. Salvato; Cameron Pittelkow; Bruce A. Linquist (Field Crops Research, 2025)

Benefits and tradeoffs of diversifying rice-based cropping systems: Impacts on soil health, productivity, and agroecosystem multifunctionality - Sara Rosenberg; Amélie C.M. Gaudin; Tommy L.D. Fenster; Whitney Brim-DeForest; Bruce Linquist; Michelle M. Leinfelder-Miles; Luis Espino; Kassim Al-Khatib; Cameron M. Pittelkow (Agriculture, Ecosystems & Environment, 2025)

Predictors of high rice yields in a high-yielding environment: Lessons from a yield contest - Bruce Linquist; Kassim Al-Khatib; Whitney Brim-DeForest; Matthew B. Espe; Luis Espino; Michelle Leinfelder-Miles; John R. Stogsdill (Field Crops Research, 2025)

Critical assessment of nitrogen use efficiency indicators: Bridging new and old paradigms to improve sustainable nitrogen management - Santiago Tamagno; Tai McClellan Maaz; Chris van Kessel; Bruce A. Linquist; Jagdish Kumar Ladha; Mark E. Lundy; Fidel Maureira; Cameron M. Pittelkow (European Journal of Agronomy, 2024)

Mid-season drain severity impacts on rice yields, greenhouse gas emissions and heavy metal uptake in grain: evidence from on-farm studies - Henry Perry; Daniela R. Carrijo; Aria H. Duncan; Scott Fendorf; Bruce A. Linquist (Field Crops Research, 2024)

Opportunities for mitigating net system greenhouse gas emissions in Southeast Asian rice production: A systematic review - Zhenglin Zhang; Ignacio Macedo; Bruce A. Linquist; Bjoern Ole Sander; Cameron M. Pittelkow (Agriculture, Ecosystems & Environment, 2024)

A geospatial assessment of soil properties to identify the potential for crop rotation in rice systems - Luke A. Salvato; Cameron M. Pittelkow; Anthony T. O’Geen; Bruce A. Linquist (Agriculture, Ecosystems & Environment, 2024)

Assessment of potassium soil balances and availability in high yielding rice systems - Bruce A. Linquist; Johnny C. Campbell; Randal J. Southard (Nutrient Cycling in Agroecosystems, 2022)
Plant demand for K in rice is comparable to nitrogen. With yields and management practices changing, refining K fertility management and decision-making tools is necessary. Our objectives were to determine (1) how soil K balances affect soil K indices, (2) the best soil test indicator of plant K availability, and (3) the relationships between plant and soil K indices. We assessed soil (plow layer) and flag-leaf samples from 55 commercial rice fields in California. Growers provided historical information on K fertility practices, straw management, and yields to develop a soil K balance. A soil K balance average of − 15 kg K ha −1 yr −1 (range: − 72 to 47) suggested an increased likelihood of K infertility; however, K balance was not correlated with soil K indices or flag-leaf K. This, plus the potential for K losses and fixation of surplus K, suggests that attempting to build up soil K may not be an effective strategy. Soil K indices were poorly correlated with plant K, but 1 N NH 4 OAc-extractable K (Kext) was the best of the K indices tested. Soils that were low in Kext had low clay content, CEC, and K saturation, a high Ca + Mg:K ratio, and showed evidence of K fixation. Soil K varied regionally and may be related to irrigation water and soil parent material. The critical level for Kext (currently 60 mg K kg −1 ) may need to be revised based on our findings, as there was evidence of K deficiencies above this concentration.

Water and air temperature impacts on rice (Oryza sativa) phenology - Hussain Sharifi; Robert J. Hijmans; James E. Hill; Bruce A. Linquist (Paddy and Water Environment, 2018)

Higher yields and lower methane emissions with new rice cultivars - Yu Jiang; Kees Jan van Groenigen; Shan Huang; Bruce A. Hungate; Chris van Kessel; Shuijin Hu; Jun Zhang; Lianhai Wu; Xiaojun Yan; Lili Wang; Jin Chen; Xiaoning Hang; et al. (Global Change Biology, 2017)
Breeding high‐yielding rice cultivars through increasing biomass is a key strategy to meet rising global food demands. Yet, increasing rice growth can stimulate methane ( CH 4 ) emissions, exacerbating global climate change, as rice cultivation is a major source of this powerful greenhouse gas. Here, we show in a series of experiments that high‐yielding rice cultivars actually reduce CH 4 emissions from typical paddy soils. Averaged across 33 rice cultivars, a biomass increase of 10% resulted in a 10.3% decrease in CH 4 emissions in a soil with a high carbon (C) content. Compared to a low‐yielding cultivar, a high‐yielding cultivar significantly increased root porosity and the abundance of methane‐consuming microorganisms, suggesting that the larger and more porous root systems of high‐yielding cultivars facilitated CH 4 oxidation by promoting O 2 transport to soils. Our results were further supported by a meta‐analysis, showing that high‐yielding rice cultivars strongly decrease CH 4 emissions from paddy soils with high organic C contents. Based on our results, increasing rice biomass by 10% could reduce annual CH 4 emissions from Chinese rice agriculture by 7.1%. Our findings suggest that modern rice breeding strategies for high‐yielding cultivars can substantially mitigate paddy CH 4 emission in China and other rice growing regions.

Point stresses during reproductive stage rather than warming seasonal temperature determine yield in temperate rice - Matthew B. Espe; Jim E. Hill; Robert J. Hijmans; Kent McKenzie; Randall Mutters; Luis A. Espino; Michelle Leinfelder‐Miles; Chris van Kessel; Bruce A. Linquist (Global Change Biology, 2017)
Climate change is predicted to shift temperature regimes in most agricultural areas with temperature changes expected to impact yields of most crops, including rice. These temperature‐driven effects can be classified into point stresses, where a temperature event during a sensitive stage drives a reduction in yield, or seasonal warming losses, where raised temperature is thought to increase maintenance energy demands and thereby decrease available resources for yield formation. Simultaneous estimation of the magnitude of each temperature effect on yield has not been well documented due to the inherent difficulty in separating their effects. We simultaneously quantified the magnitude of each effect for a temperate rice production system using a large data set covering multiple locations with data collected from 1995 to 2015, combined with a unique probability‐based modeling approach. Point stresses, primarily cold stress during the reproductive stages (booting and flowering), were found to have the largest impact on yield (over 3 Mg/ha estimated yield losses). Contrary to previous reports, yield losses caused by increased temperatures, both seasonal and during grain‐filling, were found to be small (approximately 1–2% loss per °C). Occurrences of cool temperature events during reproductive stages were found to be persistent over the study period, and within season, the likelihood of a cool temperature event increased when flowering occurred later in the season. Short and medium grain types, typically recommended for cool regions, were found to be more tolerant of cool temperatures but more sensitive to heat compared to long grain cultivars. These results suggest that for temperate rice systems, the occurrence of periodic stress events may currently overshadow the impacts of general warming temperature on crop production.

Water balances and evapotranspiration in water- and dry-seeded rice systems - Bruce Linquist; Richard Snyder; Frank Anderson; Luis Espino; Guglielmo Inglese; Serena Marras; Ruben Moratiel; Randall Mutters; Placido Nicolosi; Honza Rejmanek; Alfonso Russo; Tom Shapland; et al. (Irrigation Science, 2015)

Reducing greenhouse gas emissions, water use, and grain arsenic levels in rice systems - Bruce A. Linquist; Merle M. Anders; Maria Arlene A. Adviento‐Borbe; Rufus L. Chaney; L. Lanier Nalley; Eliete F.F. da Rosa; Chris van Kessel (Global Change Biology, 2015)
Agriculture is faced with the challenge of providing healthy food for a growing population at minimal environmental cost. Rice ( Oryza sativa ), the staple crop for the largest number of people on earth, is grown under flooded soil conditions and uses more water and has higher greenhouse gas ( GHG ) emissions than most crops. The objective of this study was to test the hypothesis that alternate wetting and drying ( AWD – flooding the soil and then allowing to dry down before being reflooded) water management practices will maintain grain yields and concurrently reduce water use, greenhouse gas emissions and arsenic (As) levels in rice. Various treatments ranging in frequency and duration of AWD practices were evaluated at three locations over 2 years. Relative to the flooded control treatment and depending on the AWD treatment, yields were reduced by GWP of CH 4 and N 2 O emissions) reduced by 45–90%, and grain As concentrations reduced by up to 64%. In general, as the severity of AWD increased by allowing the soil to dry out more between flood events, yields declined while the other benefits increased. The reduction in GWP was mostly attributed to a reduction in CH 4 emissions as changes in N 2 O emissions were minimal among treatments. When AWD was practiced early in the growing season followed by flooding for remainder of season, similar yields as the flooded control were obtained but reduced water use (18%), GWP (45%) and yield‐scaled GWP (45%); although grain As concentrations were similar or higher. This highlights that multiple environmental benefits can be realized without sacrificing yield but there may be trade‐offs to consider. Importantly, adoption of these practices will require that they are economically attractive and can be adapted to field scales.

Optimizing rice yields while minimizing yield‐scaled global warming potential - Cameron M. Pittelkow; Maria A. Adviento‐Borbe; Chris van Kessel; James E. Hill; Bruce A. Linquist (Global Change Biology, 2014)
To meet growing global food demand with limited land and reduced environmental impact, agricultural greenhouse gas ( GHG ) emissions are increasingly evaluated with respect to crop productivity, i.e., on a yield‐scaled as opposed to area basis. Here, we compiled available field data on CH 4 and N 2 O emissions from rice production systems to test the hypothesis that in response to fertilizer nitrogen (N) addition, yield‐scaled global warming potential ( GWP ) will be minimized at N rates that maximize yields. Within each study, yield N surplus was calculated to estimate deficit or excess N application rates with respect to the optimal N rate (defined as the N rate at which maximum yield was achieved). Relationships between yield N surplus and GHG emissions were assessed using linear and nonlinear mixed‐effects models. Results indicate that yields increased in response to increasing N surplus when moving from deficit to optimal N rates. At N rates contributing to a yield N surplus, N 2 O and yield‐scaled N 2 O emissions increased exponentially. In contrast, CH 4 emissions were not impacted by N inputs. Accordingly, yield‐scaled CH 4 emissions decreased with N addition. Overall, yield‐scaled GWP was minimized at optimal N rates, decreasing by 21% compared to treatments without N addition. These results are unique compared to aerobic cropping systems in which N 2 O emissions are the primary contributor to GWP , meaning yield‐scaled GWP may not necessarily decrease for aerobic crops when yields are optimized by N fertilizer addition. Balancing gains in agricultural productivity with climate change concerns, this work supports the concept that high rice yields can be achieved with minimal yield‐scaled GWP through optimal N application rates. Moreover, additional improvements in N use efficiency may further reduce yield‐scaled GWP , thereby strengthening the economic and environmental sustainability of rice systems.

Reducing rice field algae and cyanobacteria abundance by altering phosphorus fertilizer applications - David F. Spencer; Bruce A. Linquist (Paddy and Water Environment, 2014)

Underlying causes of yield spatial variability and potential for precision management in rice systems - Maegen B. Simmonds; Richard E. Plant; José M. Peña-Barragán; Chris van Kessel; Jim Hill; Bruce A. Linquist (Precision Agriculture, 2013)

Climate, duration, and N placement determine N 2 O emissions in reduced tillage systems: a meta‐analysis - Chris van Kessel; Rodney Venterea; Johan Six; Maria Arlene Adviento‐Borbe; Bruce Linquist; Kees Jan van Groenigen (Global Change Biology, 2013)
No‐tillage and reduced tillage ( NT / RT ) management practices are being promoted in agroecosystems to reduce erosion, sequester additional soil C and reduce production costs. The impact of NT / RT on N 2 O emissions, however, has been variable with both increases and decreases in emissions reported. Herein, we quantitatively synthesize studies on the short‐ and long‐term impact of NT / RT on N 2 O emissions in humid and dry climatic zones with emissions expressed on both an area‐ and crop yield‐scaled basis. A meta‐analysis was conducted on 239 direct comparisons between conventional tillage ( CT ) and NT / RT . In contrast to earlier studies, averaged across all comparisons, NT / RT did not alter N 2 O emissions compared with CT . However, NT / RT significantly reduced N 2 O emissions in experiments >10 years, especially in dry climates. No significant correlation was found between soil texture and the effect of NT / RT on N 2 O emissions. When fertilizer‐N was placed at ≥5 cm depth, NT / RT significantly reduced area‐scaled N 2 O emissions, in particular under humid climatic conditions. Compared to CT under dry climatic conditions, yield‐scaled N 2 O increased significantly (57%) when NT / RT was implemented NT / RT . There was a significant decrease in yield‐scaled N 2 O emissions in humid climates when fertilizer‐N was placed at ≥5 cm depth. Therefore, in humid climates, deep placement of fertilizer‐N is recommended when implementing NT / RT . In addition, NT / RT practices need to be sustained for a prolonged time, particularly in dry climates, to become an effective mitigation strategy for reducing N 2 O emissions.

An agronomic assessment of greenhouse gas emissions from major cereal crops - Bruce Linquist; Kees Jan van Groenigen; Maria Arlene Adviento‐Borbe; Cameron Pittelkow; Chris van Kessel (Global Change Biology, 2012)
Agricultural greenhouse gas ( GHG ) emissions contribute approximately 12% to total global anthropogenic GHG emissions. Cereals (rice, wheat, and maize) are the largest source of human calories, and it is estimated that world cereal production must increase by 1.3% annually to 2025 to meet growing demand. Sustainable intensification of cereal production systems will require maintaining high yields while reducing environmental costs. We conducted a meta‐analysis (57 published studies consisting of 62 study sites and 328 observations) to test the hypothesis that the global warming potential ( GWP ) of CH 4 and N 2 O emissions from rice, wheat, and maize, when expressed per ton of grain (yield‐scaled GWP ), is similar, and that the lowest value for each cereal is achieved at near optimal yields. Results show that the GWP of CH 4 and N 2 O emissions from rice (3757 kg CO 2 eq ha −1 season −1 ) was higher than wheat (662 kg CO 2 eq ha −1 season −1 ) and maize (1399 kg CO 2 eq ha −1 season −1 ). The yield‐scaled GWP of rice was about four times higher (657 kg CO 2 eq Mg −1 ) than wheat (166 kg CO 2 eq Mg −1 ) and maize (185 kg CO 2 eq Mg −1 ). Across cereals, the lowest yield‐scaled GWP values were achieved at 92% of maximal yield and were about twice as high for rice (279 kg CO 2 eq Mg −1 ) than wheat (102 kg CO 2 eq Mg −1 ) or maize (140 kg CO 2 eq Mg −1 ), suggesting greater mitigation opportunities for rice systems. In rice, wheat and maize, 0.68%, 1.21%, and 1.06% of N applied was emitted as N 2 O , respectively. In rice systems, there was no correlation between CH 4 emissions and N rate. In addition, when evaluating issues related to food security and environmental sustainability, other factors including cultural significance, the provisioning of ecosystem services, and human health and well‐being must also be considered.

Benefits of organic residues and chemical fertilizer to productivity of rain-fed lowland rice and to soil nutrient balances - Bruce A. Linquist; Vongvilay Phengsouvanna; Pheng Sengxue (Nutrient Cycling in Agroecosystems, 2007)